Pendampingan Penguatan Ekonomi Dan Ketahanan Pangan Masyarakat Melalui Program “Melak Warung Di Buruan”Di Desa Bungurjaya Pondoksalam Purwakarta - Sopian, Ahmad Ali (STIE Syariah Indonesia Purwakarta, 2023)
Pondoksalam District, Purwakarta Regency as one of the areas with potential agricultural products. Several leading commodities such as petai, mangosteen, rice, cassava, bananas and vegetables are sourced from the sub-district. unfortunately the magnitude of the natural potential has not been utilized optimally. Several commodity spices such as chili, red cayenne, tomatoes, onions and vegetables are still obtained by buying. Under certain conditions, such as during the holidays, these prices may increase. Thus the burden of kitchen maintenance costs is quite a big risk to community household expenses. This Community Service Program was carried out in Bungurjaya Village, Pondoksalam District with the aim of being able to encourage community productivity to build village food self-sufficiency through the Assistance program for strengthening the economy. This assistance uses counseling methods, training and management practices. The results of this program encourage the community to maximize vacant land into plantation land by planting vegetables and kitchen spices, increasing maintenance through fertilizers and liquid organic waste from utilizing kitchen organic waste so as to reduce maintenance costs. The realization of the economic resilience of the village community through the yard which provides kitchen materials for free and can be traded to increase the value of heating the community's economy